Prevalence and pattern of internet addiction among medical students, Bengaluru - S. C., Ranganatha; S., Usha (International Journal Of Community Medicine And Public Health, 2017)
Background: Currently internet has become an important tool for education, entertainment and communication. Increased internet usage may lead to point of habituation, addiction, adverse academic, mental, physical and social effects. Medical students are also among the vulnerable group on account of time they spend on internet, hence this study was undertaken among medical students. The objective of the study was to estimate the prevalence and pattern of internet addiction among first year medical students. Methods: A Cross sectional study was conducted among the first year medical students of Rajarajeswari Medical College and Hospital, Bengaluru. The sample size calculated was 125 as per the prevalence of internet addiction among medical students as 58.87% found in the study by Chaudhari et al. A total of 140 students present in the class at the time of data collection, who consented were considered for the study. Semi structured questionnaire with Young’s 8-item questionnaire and 20-item internet addiction scale was administered to the students. The data was analyzed using SPSS version 21.0. Pearson’s chi-square test was applied to know the association between two variables. Results: Out of 140 study subjects, majority (73.57%) were 18 yrs of age, 62.14% were females. 81 (57.86%) were hostelites. 77 (55%) of students were using internet for 4-6 hrs per day. 80 (57.14%) students have been using internet for more than 5 yrs. The prevalence of internet addiction according to Young’s 8-item questionnaire was 66 (47.14%) out of 140. Out of the 66, most common gadget used was mobile and most common purpose was social networking. The most common pattern of internet addiction according to Young’s 20-item scale was possible addict (49.29%). Internet addiction among localites was observed to be more than hostelites, this association was found to be statistically significant. Conclusions: Internet addiction was found to be substantial among medical students and most common purpose of internet usage was for social networking.